Removal of variable domain N-linked glycosylation as a means to improve the homogeneity of HIV-1 broadly neutralizing antibodies. Issue 1 (1st January 2020) - Chuang, Gwo-Yu; Asokan, Mangaiarkarasi; Ivleva, Vera B.; Pegu, Amarendra; Yang, Eun Sung; Zhang, Baoshan; Chaudhuri, Rajoshi; Geng, Hui; Lin, Bob C.; Louder, Mark K.; McKee, Krisha; O'Dell, Sijy; et al.
ABSTRACT: Broadly neutralizing antibodies are showing promise in the treatment and prevention of HIV-1, with several now being evaluated clinically. Some lead clinical candidates, including antibodies CAP256-VRC26.25, N6, PGT121, and VRC07-523, have one or more N -linked glycosylation sequons in their variable domains (Fvs) from somatic hypermutation, and these glycans increase chemical heterogeneity, complicating the manufacture of these antibodies as products. Here we propose a general method to remove Fv glycans and use this method to develop engineered versions of these four antibodies with Fv glycans removed. When germline residues were introduced to remove each glycan, antibody properties between wild type and mutant were not significantly altered for CAP256-VRC26.25 and PGT121; however, germline mutants for N6 and VRC07-523 showed increased polyreactivity, which is known to correlate with unfavorable in vivo pharmacokinetics. To reduce polyreactivity induced by removal of Fv glycan, we mutated aromatic residues and arginines structurally proximal to the removed glycan and identified Fv glycan-removed variants with low polyreactivity for N6 and VRC07-523. Two such variants, N6-N72LC Q-R18LC D and VRC07-523-N72LC Q-R24LC D, showed thermostability, neutralization potency and breadth, and half-life in humanized FcRn mice that were similar to their wild-type Fv-glycosylated counterparts. The removal of Fv glycan and reduction of chemical heterogeneity were confirmed by liquid chromatography-mass spectrometry. With reduced heterogeneity, the Fv-glycan-removed variants developed here may have utility as products for treating or preventing infection by HIV-1.